2001
DOI: 10.1046/j.1440-1703.2001.00445.x
|View full text |Cite
|
Sign up to set email alerts
|

Local neighborhood effects on long‐term survival of individual trees in a neotropical forest

Abstract: The survival of approximately 235 000 individual tropical trees and saplings in the 50 ha permanent plot on Barro Colorado Island (BCI), Panama was analyzed over a 13‐year interval (1982–1995) as a function of four biotic neighborhood variables: (i) total stem density; (ii) conspecific density; (iii) relative plant size; and (iv) relative species richness. These neighborhood variables were measured in annular rings of width 2.5 m, extending 30 m from a given focal plant, and in one more distant annulus at 47.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
283
3
12

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 279 publications
(304 citation statements)
references
References 24 publications
6
283
3
12
Order By: Relevance
“…However, most other studies of seedling and sapling growth and survival in forests have similarly detected density-dependent effects at scales < 30 m (Curran and Webb 2000, Hubbell et al 2001, Peters 2003, Uriarte et al 2004b, Comita and Hubbell 2009). …”
Section: Accepted Ar Ticlementioning
confidence: 93%
“…However, most other studies of seedling and sapling growth and survival in forests have similarly detected density-dependent effects at scales < 30 m (Curran and Webb 2000, Hubbell et al 2001, Peters 2003, Uriarte et al 2004b, Comita and Hubbell 2009). …”
Section: Accepted Ar Ticlementioning
confidence: 93%
“…Characteristics of tree neighbourhood are closely related to competition intensity and mortality risk (Hubbell et al, 2001;Uriarte et al, 2004). However, most of the research has been carried out on monospecific stands (Dobbertin et al, 2001;Drobyshev et al, 2007;Monserud and Sterba 1999), with relative less attention being focused on mixed forests where the effect of neighbour identity creates a much more complex picture (Hubbell et al, 2001;Yao et al, 2001;Zhao et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Such a relationship between plant performance and neighbourhood weight is not surprising, although success in demonstrating the phenomenon has been rather variable in the past. Early work by Kira et al (1953) found the weight of regularly spaced plants to be correlated with the mean weight of the plant's six nearest neighbours, and several subsequent studies also found a relationship between plant growth and neighbourhood properties (Mithen et al 1984;Weiner 1984;Silander & Pacala 1985;Stoll et al 1994;Hubbell et al 2001;Stoll & Bergius 2005). However, such relationships have sometimes proved harder to demonstrate in the field (Martin & Ek 1984;Coomes et al 2002), especially when plants are regularly spaced (Lorimer 1983;Wimberly & Bare 1996; but see also Larocque 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Although Bayesian data analysis is not yet widely used in ecology (Ellison 2004), recent applications of Bayesian techniques to spatial problems in plant ecology, including neighbourhood-dependent survival of trees in a tropical rain forest (Hubbell et al . 2001), tree fecundity (Clark et al .…”
Section: Introductionmentioning
confidence: 99%